Elevating Pedagogical Outcomes: A Study on the Efficacy of State Islamic Religious Universities Management in Aceh, Indonesia - Muhammad Anggung Manumanoso Prasetyo; Anjas Baik Putra; Faizal Luqman; Minhajul Abidin Mank (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This research aims to examine the efficacy of higher education administration in quality control of Islamic university lecturers in Aceh. Method: The study employs a qualitative paradigm, with data gathered through observation, interview findings, and documentation. Informants include campus policymakers (rectors, deans, and department heads) and numerous students who are users. Results: Quality planning outcomes are provided through research under the institution's vision, purpose, and objectives. Planning, revision, and verification are used to carry out the program. Its substance encourages attempts to strengthen educational quality control but does not specify the desired results. Quality control management for lecturers is controlled by each component (faculties and departments) using formal and written references. The projected consequences of senior policy managers being able to design an integrity-based university governance model based on enhancing organizational values, norms, laws, management, and organizational structures. Novelty: Quality control model novelty consists of five stages, namely (1) control principles, (2) quality implementation, (3) professionalism development, (4) evaluation monitoring, and (5) collaboration strategy.